2007
DOI: 10.1086/510575
|View full text |Cite
|
Sign up to set email alerts
|

A Check for Consistency between Different Magnetic Helicity Measurements Based on the Helicity Conservation Principle

Abstract: Magnetic helicity is a useful quantity in characterizing the magnetic systems of solar active regions. The purpose of the present work is to check for consistency between the local correlation tracking (LCT) method used to measure helicity injection through the photosphere, and the linear force-free field (LFFF) method used to determine helicity in the corona, based on the principle of helicity conservation in the solar corona. We have calculated the amount of magnetic helicity injected through the photosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…This provides an estimation independent of the helicity injection computed above. The equivalent number of turns typically ranges from 0.1 to 0.2 Green et al, 2002;Mandrini et al, 2005;Lim et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This provides an estimation independent of the helicity injection computed above. The equivalent number of turns typically ranges from 0.1 to 0.2 Green et al, 2002;Mandrini et al, 2005;Lim et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…For our purpose, we only need to know the integral of the helicity flux densities, while the pattern of the helicity flux is not important for this. Note that Lim et al (2007) compared the consistency of the use of the LCT method to measure magnetic helicity injection through the photosphere and that of the LFFF method to determine helicity. Their results support the reliability of previous method determining the injected helicity.…”
Section: Helicitymentioning
confidence: 99%
“…These features seem to be invariant with respect to solar cycle, as would be predicted by helical dynamos, even when the field itself reverses sign. Note also that Hα filaments seem to exhibit dextral (right handed) twist in North and sinstral (left handed) in south (Martin and McAllister 1997) BUT: right handed Hα filaments may be supported by left handed fields and vice versa (Rust 1999) There have been efforts to measure the rate of injection of magnetic helicity (Chae 2004;Schuck 2005;Lim et al 2007), particularly, its gauge invariant cousin: the "relative magnetic helicity" (Berger & Field 1984; the difference between actual magnetic helicity and that of a potential field) by tracking footpoint motions. It can be shown that the footprint motions provide a direct measure of this input rate (Démoulin & Berger 2003).…”
Section: Helicity Fluxes In Galactic and Stellar Contextsmentioning
confidence: 99%